Shattered midnight ebook - Clayton, Dhonielle (The Mirror, 2022)
The Mirror: Shattered Midnight is the second novel in the innovative four-book fairy-tale series written by Julie C. Dao, Dhonielle Clayton, J.C. Cervantes, and L. L. McKinney, following one family over several generations, and the curse that plagues it. Zora Broussard has arrived in New Orleans with not much more than a bag of clothes, a beautiful voice, and a pair of enchanted red shoes. Running from a tragic accident caused by her magic, Zora wants nothing more than to blend in, as well as to avoid her overbearing aunt and mean-spirited cousins. Music becomes Zora's only means of escape, yet she wonders if she should give it all up to remove the powers that make her a target, especially as a Black woman in the South. But when Zora gets the chance to perform in a prominent jazz club, she meets a sweet white pianist named Phillip with magic of his own, including a strange mirror that foretells their future together. Falling into a forbidden love, Zora and Phillip must keep their relationship a secret. And soon the two discover the complicated connection between their respective families, a connection that could lead to catastrophe for them both. In the era of segregation and speakeasies, Zora must change her destiny and fight for the one she loves . . . or risk losing everything.